Amplification of Plunging Flows in Bedrock Canyons - Max Hurson; Jeremy G. Venditti; Colin D. Rennie; Eva Kwoll; Kirsti Fairweather; Dan R. W. Haught; Kyle M. Kusack; Michael Church (Geophysical Research Letters)
Abstract Bedrock river erosion is driven by channel hydraulics, which are not well understood for complex morphologies. Many bedrock rivers exhibit a constriction‐pool‐widening (CPW) morphology associated with submerged plunging flows. These flows cause velocity profile inversions resulting in high velocities near the bed and low velocities on the water surface. The first observations documenting plunging flows were from relatively low discharge, and it is unclear whether they persist during floods. Here we show that plunging flows persist and get stronger at flood discharge, increasing bedrock erosion potential by particle impacts. Flood‐discharge plunging flows contact the bed and maintain high velocities farther through the CPW structure, and evacuate large volumes of sediment from the pools. These reach‐scale processes are not represented in large‐scale landscape evolution models, yet these erosion mechanisms set the pace of landscape evolution, begging for a re‐evaluation of process representation in landscape evolution models.